2015
DOI: 10.1007/s11356-015-4813-z
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of heavy metals in tropical fish and shellfish collected from the river Buriganga, Bangladesh

Abstract: Although fish, crustacean, and shellfish are significant sources of protein, they are currently affected by rapid industrialization, resulting in increased concentrations of heavy metals. Accumulation of heavy metals (V, Cr, Mn, Ni, Cu, Zn, As, Se, Mo, Ag, Cd, Sb, Ba, and Pb) and associated human health risk were investigated in three fish species, namely Ailia coila, Gagata youssoufi, and Mastacembelus pancalus; one crustacean (prawn), Macrobrachium rosenbergii; and one Gastropoda, Indoplanorbis exustus, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(124 citation statements)
references
References 41 publications
9
101
3
1
Order By: Relevance
“…A fairly lower Pb level was reported in canned mussels from the Canary Islands ranging from 0.006 to 0.008 mg/kg (Gutierrez et al 2004). This study also indicated the lower concentration of Pb in crustacean (ND-0.04 mg/kg) or mollusk (ND-0.10 mg/kg) than the results reported by .20 mg/kg) (Figueira et al 2011) and Ahmed et al (4.55 ± 0.11 mg/kg) (Ahmed et al 2015). According to the previous literatures, the Pb concentration in fish (30.7 mg/kg) from Lingdingyang, crustacean (12.0 mg/kg) from Guangxi, and mollusk (6.0 mg/kg) from Hong Kong was extremely high (Wang et al 2013).…”
Section: Heavy Metal Concentrationssupporting
confidence: 62%
See 2 more Smart Citations
“…A fairly lower Pb level was reported in canned mussels from the Canary Islands ranging from 0.006 to 0.008 mg/kg (Gutierrez et al 2004). This study also indicated the lower concentration of Pb in crustacean (ND-0.04 mg/kg) or mollusk (ND-0.10 mg/kg) than the results reported by .20 mg/kg) (Figueira et al 2011) and Ahmed et al (4.55 ± 0.11 mg/kg) (Ahmed et al 2015). According to the previous literatures, the Pb concentration in fish (30.7 mg/kg) from Lingdingyang, crustacean (12.0 mg/kg) from Guangxi, and mollusk (6.0 mg/kg) from Hong Kong was extremely high (Wang et al 2013).…”
Section: Heavy Metal Concentrationssupporting
confidence: 62%
“…According to health risk assessment model (USEPA 2011), the possible health risk caused by seafood consumption of coastal residents was appraised using the method of target hazard quotient (THQ) (Storelli 2008;Yu et al 2014;Ahmed et al 2015). Herein, THQ is defined as the ratio of daily seafood consumption rate in relation to maximum allowable seafood consumption rate considering the carcinogenic and non-carcinogenic effects of the heavy metals, see formulas (2) and (3), respectively:…”
Section: Health Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the turbulence created by increase of flow, some sediment are carried away and displaced from the river bottom. During the Dry season (April experience Minimal rainfall as compared to June) Evaporation and temperature tend to be higher than in raining season which is in line with Ahmed et al [64].…”
Section: Discussionsupporting
confidence: 84%
“…Heavy metals are ubiquitous in the environment from either natural or anthropogenic interventions that can pollute soil, water and plants including other compartments of the ecosystem and eventually affect human health and well-being (Roychowdhury et al 2003;Buschmann et al 2008;Bundschuh et al 2012;Ahmed et al 2015).…”
Section: Introductionmentioning
confidence: 99%